Effectiveness of a virtual reality nursing simulation for pediatric pneumonia care: a Korean pilot study using a single-group pre-post test design. - Kim, Eun Joo; Kim, Seong Kwang; Song, Sung Sook (Child Health Nursing Research, 2025)
Purpose: This pilot study aimed to develop a virtual reality (VR) nursing simulation for pediatric pneumonia care tailored to the Korean clinical context and evaluate its educational effectiveness for nursing students. Methods: A single-group pretest--posttest design was employed with 20 senior nursing students from April to May 2025. The intervention was a 70-minute VR nursing simulation of pediatric pneumonia care, structured with pre-briefing, a main scenario, and debriefing. Data were collected on participants' knowledge of pediatric pneumonia, clinical judgment (Nursing Clinical Judgment Scale), and simulation effectiveness (Simulation Effectiveness Tool-Modified) before and after the intervention. Usability (User Experience Questionnaire) and qualitative feedback were collected after the intervention. Prepost comparisons were performed using paired t-tests. Results: The program did not yield a statistically significant change in knowledge scores (p=.893). However, there were significant improvements in the mean scores for clinical judgment (p<.001) and simulation effectiveness (p=.013). A qualitative analysis revealed that, while the participants found the experience immersive and realistic, they also reported operational difficulties, indicating the need for usability improvements. Conclusion: The VR nursing simulation is a promising pedagogical tool for enhancing nursing students' clinical judgment and perceived learning effectiveness in a Korean pediatric context. The findings suggest that, while the intervention was effective in improving practical reasoning, future iterations should focus on reinforcing knowledge acquisition and optimizing user experience to maximize the educational impact.